Reconfigurable intelligent surfaces for THz: Hardware impairments and switching technologies - Matos, S.; Yihan Ma; Qi Luo; Deuermeier, J.; Lucci, L.; Gavriilidis, P.; Kiazadeh, A.; Lain-Rubio, V.; Phan, T.; Soh, P.; Clemente, A.; Pessoa, L.; et al. (Proceedings of the International Conference on Electromagnetics in Advanced Applications, ICEAA, 2024)
The demand for unprecedented performance in the upcoming 6 G wireless networks is fomenting the research on THz communications empowered by Reconfigurable Inteligent Surfaces (RISs). A wide range of use cases have been proposed, most of them, assuming high-level RIS models that overlook some of the hardware impairments that this technology faces. The expectation is that the emergent reconfigurable THz technologies will eventually overcome its current limitations. This disassociation from the hardware may mask nonphysical assumptions, perceived as hardware limitations. In this paper, a top-down approach bounded by physical constraints is presented, distilling from system-level specifications, hardware requirements, and upper bounds for the RIS-aided system performance. We consider D-band indoor and outdoor scenarios where a more realistic assessment of the state-of-the-art solution can be made. The goal is to highlight the intricacies of the design procedure based on sound assumptions for the RIS performance. For a given signal range and angular coverage, we quantify the required RIS size, number of switching elements, and maximum achievable bandwidth and capacity.